2017
DOI: 10.3847/1538-4357/834/2/198
|View full text |Cite
|
Sign up to set email alerts
|

On the Newtonian and Spin-Induced Perturbations Felt by the Stars Orbiting Around the Massive Black Hole in the Galactic Center

Abstract: The S-stars discovered in the Galactic center (GC) are expected to provide unique dynamical tests of the Kerr metric of the massive black hole (MBH) orbited by them. In order to obtain unbiased measurements of its spin and the related relativistic effects, a comprehensive understanding of the gravitational perturbations of the stars and stellar remnants around the MBH is quite essential. Here, we study the perturbations on the observables of a typical target star, i.e., the apparent orbital motion and the reds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…In order to detect black hole spin, closer stars are needed to overcome gravitational perturbations from other stars/remnants Zhang & Iorio 2017). For average black hole spin angle parameters, we found that the hypothetical star would have to satisfy a orb (1−e 2 ) 3/4 300RS T 4years N obs 120 0.25 10µas σx χ 0.9 (6.1) in order to allow detection of black hole spin.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In order to detect black hole spin, closer stars are needed to overcome gravitational perturbations from other stars/remnants Zhang & Iorio 2017). For average black hole spin angle parameters, we found that the hypothetical star would have to satisfy a orb (1−e 2 ) 3/4 300RS T 4years N obs 120 0.25 10µas σx χ 0.9 (6.1) in order to allow detection of black hole spin.…”
Section: Discussionmentioning
confidence: 98%
“…Even though these two effects could potentially be separated (e.g. astrometric deviations due to spin are maximum at apastron whereas Newtonian perturbations peak during periastron, Zhang & Iorio 2017), disentangling them with limited observations and without prior knowledge on the perturbers would be very challenging. From the diffuse light background from faint stars that cannot be currently resolved, Schödel et al (2018) estimated a total enclosed stellar mass of ∼ 180M within 250 mas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations